The approach of the ancients in dealing with dialects and the position of modernists - Al-Bab, Ibrahim; Samol , Mehran (Latakia University Journal - Arts and Humanities Sciences Series, 2018)
The subject of dialects in Arabic grammar is a subject of confusion and confusion at the time of Arabic grammar when they used the term "dialect" and "language" in their expression of the dialectic differences between the tribes. The modernists, moreover, did not have independent works, which were specialized in studying each dialect separately. They identified the clear tribes that could be adopted in their language, and left the other tribes under the pretext of leaving the linguistic level. Therefore, my dependence on this research will focus on two issues: The ancients in their dealings with dialects, relying on what was in the book properties of Ibn-taking, book Sibawayh, book Alsahabay in the jurisprudence of the language of IbnFaris, a book brief cooler and other books on this subject, and the second: modern attitude and the most prominent criticism of the approach to the ancients.